Ectopic pinealoma: an unusual clinical presentation and a histochemical comparison with a seminoma of the testis. Issue 5 (October 1973) - Beeley, J. M.; Daly, J. J.; Timperley, W. R.; Warner, J.
Abstract : A patient with ectopic pinealoma first presented with apparent anorexia nervosa and hypernatraemic coma. A history of diabetes insipidus two months previously was not known on admission to hospital. The diabetes insipidus was unmasked by the administration of steroids. Neuroendocrinal and neuropathological aspects of the case are discussed with reference to the march of symptoms due to the growth of the tumour. Histochemical evidence is presented supporting the similarity between ectopic pinealoma and seminoma which suggests that they may more properly be referred to as atypical teratomas.